2015
DOI: 10.1115/1.4029175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Unsteady Flow Field in a Vaned Diffuser of a High-Speed Centrifugal Compressor

Abstract: Vaned diffusers in centrifugal compressor stages are used to achieve higher stage pressure ratios, higher stage efficiencies, and more compact designs. The interaction of the stationary diffuser with the impeller can lead to resonant vibration with potentially devastating effects. This paper presents unsteady diffuser vane surface pressure measurements using in-house developed, flush mounted, fast response piezoresistive pressure transducers. The unsteady pressures were recorded for nine operating conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As a consequence of the non-uniformity induced by considerable impeller-diffuser interaction, the deterioration of the diffuser inlet flow was suggested to restrict the pressurization of the compressor. Vogel et al 7 used high-response transducers to investigate transient behaviors in the diffuser. Their results revealed that the high intensity of impeller-diffuser interaction spreads all along the diffuser vane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the non-uniformity induced by considerable impeller-diffuser interaction, the deterioration of the diffuser inlet flow was suggested to restrict the pressurization of the compressor. Vogel et al 7 used high-response transducers to investigate transient behaviors in the diffuser. Their results revealed that the high intensity of impeller-diffuser interaction spreads all along the diffuser vane.…”
Section: Introductionmentioning
confidence: 99%
“…Vogel et al. 7 used high-response transducers to investigate transient behaviors in the diffuser. Their results revealed that the high intensity of impeller–diffuser interaction spreads all along the diffuser vane.…”
Section: Introductionmentioning
confidence: 99%
“…Gallier, Lawless, and Fleeter (2010) found that there is a highly nonuniform flow field in the vaneless space between the impeller and the diffuser that results in a large variation in the flow angle at the diffuser vane leading edge and subsequently causes an unsteady vane loading. Vogel, Abhari, and Zemp (2014) indicated that with an increase in the flow coefficient, the pressure fluctuation amplitude decreases in the diffuser passage. Zhao et al (2015) employed CFD techniques to analyze the interaction of the inlet guide vane and the impeller, observing two loading peaks at the impeller blade leading edge for a small mass flow coefficient during a passage cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Burguburu and le Pape 22 reported the numerical aerodynamic optimization of a transonic compressor, and found that the suction of a 2D blade is optimized with a significant efficiency improvement. Vogel et al 23 carried out unsteady numerical simulation of centrifugal compressor, and found that the inlet pressure fluctuation is as high as 34.4%. Rao et al 24 found that TVD with radius ratio of 1.10 and impeller diffuser is the optimal configuration under the condition of blade tip Mach number of 0.35.…”
Section: Introductionmentioning
confidence: 99%